FORMULASI SEDIAAN GUMMY CANDIES INFUSA BUAH KARAMUNTING (Rhodomyrtus tomentosa (AITON) HASSK.) - Rakhmatullah, Aditya Noviadi; Chandra, M. Andi (Universitas Borneo Lestari, 2025)
Karamunting plant (R. tomentosa) (Aiton) Hassk.) is a plant that can be used as a source of natural antioxidants. Karamunting contains active compounds of natural antioxidants such as flavonoids. The purpose of this study was to find out the best formula based on the physical characteristics of the karamunting fruit infusion gummy candies preparation with different gelatin content and to determine the level of respondent's preference for the karamunting fruit infusion gummy candies preparation. The gummy candies formulation was made with variations in gelatin concentration of 7%, 9%, 10%, and 11%. The physical evaluations carried out included organoleptic tests, pH tests, water content tests, weight uniformity tests, elasticity tests, and hedonic tests. The organoleptic results showed that F1 and F2 were green in color, tasted not sweet, had a melon aroma, were semi-solid, and had a texture that was easily crushed or not chewy. F3 and F4 are green in color, taste less sweet and sweet, melon aroma, semi-solid, chewy texture, evaluation of gummy candies preparations shows pH 5.01-6.38, but the water content exceeds the requirements, namely 92.59% -58.11%. Based on the results of the study, it was concluded that based on the physical characteristics of the gummy candies infusion preparation of karamunting fruit, formula III met the requirements based on the results of the physical test of the preparation and became the most preferred formula based on the hedonic test